Octagon inscribed in a rectangle.

Geometry Level 3

An octagon with all equal sides is formed by cutting four congruent right triangles from each corner of the above rectangle with side lengths w w and w 2 w - 2 .

Find the value of w w for which the side length of the octagon is 51 5 \sqrt{51} - 5 .


The answer is 6.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

4 solutions

Chris Lewis
Mar 30, 2020

Let the pink sides of the four right-angled triangles be a > b a>b and the side of the octagon (given) be s s , so that 2 a + s = w 2a+s=w and 2 b + s = w 2 2b+s=w-2 . Also, by Pythagoras, a 2 + b 2 = s 2 a^2+b^2=s^2 .

Since we want to find w w , we'll eliminate a a and b b . For convenience below, write x = w s x=w-s : 2 a = x 2 b = x 2 4 a 2 + 4 b 2 = x 2 + ( x 2 ) 2 = 4 s 2 \begin{aligned} 2a &=x \\ 2b &= x-2 \\ 4a^2+4b^2 &=x^2+(x-2)^2=4s^2 \end{aligned}

Tidying up and solving, x = 1 ± 2 s 2 1 x=1 \pm \sqrt{2s^2-1} . Clearly we can ignore the negative root; so we find w = s + 1 + 2 s 2 1 = 6 w=s+1+\sqrt{2s^2-1}=\boxed6


The simplest way to find s + 1 + 2 s 2 1 s+1+\sqrt{2s^2-1} is by considering the quadratic that s s solves; we have ( s + 5 ) 2 = 51 (s+5)^2=51 , which can be rewritten as s 2 = 26 10 s s^2=26-10s .

Now, 2 s 2 1 = 51 20 s = ( s + 5 ) 2 20 s = ( s 5 ) 2 2s^2-1=51-20s=(s+5)^2-20s=(s-5)^2 , and, noting that s < 5 s<5 , the rest is easy.

Chew-Seong Cheong
Mar 29, 2020

Let the side lengths of the legs of the right triangle cut off be a a and b b as seen. Then,

{ w = 2 a + 51 5 . . . ( 1 ) w 2 = 2 b + 51 5 . . . ( 2 ) ( 1 ) ( 2 ) : 2 a 2 b = 2 b = a 1 \begin{cases} w = 2a + \sqrt{51} - 5 & ...(1) \\ w-2 = 2b + \sqrt{51} - 5 & ...(2) \end{cases} \implies (1) - (2): \quad 2a - 2b = 2 \implies b = a-1

Note that:

a 2 + b 2 = ( 51 5 ) 2 2 a 2 2 a + 1 = 76 10 51 2 a 2 2 a 75 + 10 51 = 0 \begin{aligned} a^2 + b^2 = (\sqrt{51}-5)^2 \\ 2a^2 - 2a + 1 & = 76 - 10\sqrt{51} \\ 2a^2 - 2a - 75+10\sqrt{51} & = 0 \end{aligned}

The roots to the quadratic equation are a a and b b . By Vieta's formula, a + b = 1 a+b = 1 . Let a = 1 2 + u a = \frac 12 + u and b = 1 2 u b=\frac 12 - u , then

( 1 2 + u ) ( 1 2 u ) = 10 51 75 2 ( u + 1 2 ) ( u 1 2 ) = 75 10 51 2 u 2 1 4 = 75 10 51 2 u 2 = 151 20 51 4 u = 10 51 2 a = u + 1 2 = 11 51 2 w = 2 a + 51 5 = 6 \begin{aligned} \left(\frac 12 + u \right)\left(\frac 12 - u \right) & = \frac {10\sqrt{51}-75}2 \\ \left(u + \frac 12\right)\left(u-\frac 12 \right) & = \frac {75-10\sqrt{51}}2 \\ u^2 - \frac 14 & = \frac {75-10\sqrt{51}}2 \\ u^2 & = \frac {151-20\sqrt{51}}4 \\ \implies u & = \frac {10 - \sqrt{51}}2 \\ \implies a & = u + \frac 12 = \frac {11-\sqrt{51}}2 \\ \implies w & = 2a + \sqrt{51} - 5 = \boxed 6 \end{aligned}

Rocco Dalto
Mar 29, 2020

w 2 x = w 2 2 y x y = 1 y = x 1 w - 2x = w - 2 - 2y \implies x - y = 1 \implies y = x - 1

and

x 2 + y 2 = ( w 2 x ) 2 x 2 + ( x 1 ) 2 = w 2 4 w x + 4 x 2 x^2 + y^2 = (w - 2x)^2 \implies x^2 + (x - 1)^2 = w^2 - 4wx + 4x^2 \implies

2 x 2 2 ( 2 w 1 ) x + w 2 1 = 0 x = 2 w 1 ± 2 w 2 4 w + 3 2 2x^2 - 2(2w - 1)x + w^2 - 1 = 0 \implies x = \dfrac{2w - 1 \pm \sqrt{2w^2 - 4w + 3}}{2}

Using x = 2 w 1 + 2 w 2 4 w + 3 2 w 2 x < 0 : x = \dfrac{2w - 1 + \sqrt{2w^2 - 4w + 3}}{2} \implies w - 2x < 0:

w 2 x = 1 w 2 w 2 4 w + 3 w - 2x = 1 - w - \sqrt{2w^2 - 4w + 3} and ( 1 w ) 2 ( 2 w 2 4 w + 3 ) = (1 - w)^2 - (2w^2 - 4w + 3) =

( w 2 2 w + 2 ) < 0 -(w^2 - 2w + 2) < 0 for all real w w

1 w < 2 w 2 4 w + 3 \implies |1 - w| < \sqrt{2w^2 - 4w + 3} \therefore we drop x = 2 w 1 + 2 w 2 4 w + 3 2 x = \dfrac{2w - 1 + \sqrt{2w^2 - 4w + 3}}{2}

and choose x = 2 w 1 2 w 2 4 w + 3 2 x = \dfrac{2w - 1 - \sqrt{2w^2 - 4w + 3}}{2} \implies

w 2 x = 1 w + 2 w 2 4 w + 3 = 51 5 w - 2x = 1 - w + \sqrt{2w^2 - 4w + 3} = \sqrt{51} - 5 \implies

2 w 2 4 w + 3 = ( ( 51 6 ) + w ) 2 = 87 12 51 + 2 ( 51 6 ) w + w 2 2w^2 - 4w + 3 = ((\sqrt{51} - 6) + w)^2 = 87 - 12\sqrt{51} + 2(\sqrt{51} - 6)w + w^2 \implies

w 2 + ( 8 2 51 ) w + 12 51 84 = 0 w^2 + (8 - 2\sqrt{51})w + 12\sqrt{51} - 84 = 0 \implies

w = 8 + 2 51 ± 2 151 20 51 2 = w = \dfrac{-8 + 2\sqrt{51} \pm 2\sqrt{151 - 20\sqrt{51}}}{2} = 8 + 2 51 ± 2 ( 10 51 ) 2 2 = \dfrac{-8 + 2\sqrt{51} \pm 2\sqrt{(10 - \sqrt{51})^2}}{2} =

8 + 2 51 ± ( 10 51 ) 2 = 6 , 14 + 2 51 \dfrac{-8 + 2\sqrt{51} \pm (10 - \sqrt{51})}{2} = 6, -14 + 2\sqrt{51}

w = 2 51 14 w 2 < 0 w = 2\sqrt{51} - 14 \implies w - 2 < 0 \therefore choose w = 6 \boxed{w = 6}

Mahdi Raza
Apr 20, 2020

( w ( 51 5 ) 2 ) 2 + ( ( w 2 ) ( 51 5 ) 2 ) 2 = ( 51 5 ) 2 w = 6 \begin{aligned} \bigg(\frac{w-(\sqrt{51}-5)}{2}\bigg)^2 + \bigg(\frac{(w-2) - (\sqrt{51} - 5)}{2}\bigg)^2 &= (\sqrt{51}-5)^2 \\ \implies w &= \boxed{6} \end{aligned}

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...